1993
DOI: 10.1007/bf01606433
|View full text |Cite
|
Sign up to set email alerts
|

Localization of epidermal growth factor/transforming growth factor-α receptor in the human gastric mucosa

Abstract: Current evidence indicates that epidermal growth factor (EGF) and transforming growth factor-alpha (TGF-alpha) play a pivotal role in the maintenance of gastric mucosal integrity, via binding to a common cell-surface receptor (EGF/TGF-alpha receptor). We examined the distribution and cellular sites of synthesis of EGF/TGF-alpha receptor in normal human gastric mucosa by immunohistochemical and in situ hybridization techniques. Intense EGF/TGF-alpha receptor immunoreactivity was observed in the basal cytoplasm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
1
14
0
1
Order By: Relevance
“…In this tissue, the EGF-R is prevalently distributed along the basolateral membrane of surface and glandular cells while it is scarcely present on the luminal membrane (Orsini et al, 1993;Playford et al, 1996;Tarnawski et al, 1991) ( Fig. 3A and B).…”
Section: Epidermal Growth Factor and Transforming Growth Factor-alphamentioning
confidence: 95%
“…In this tissue, the EGF-R is prevalently distributed along the basolateral membrane of surface and glandular cells while it is scarcely present on the luminal membrane (Orsini et al, 1993;Playford et al, 1996;Tarnawski et al, 1991) ( Fig. 3A and B).…”
Section: Epidermal Growth Factor and Transforming Growth Factor-alphamentioning
confidence: 95%
“…When extracted from human urine, EGF/URO inhibits human gastric acid secretion and is effective in the stimulation of cell proliferation in response to injury; this has important implications in healing of damaged gastric mucosa and in the rat EGF accelerates ulcer healing due to its mitogenic activity (Konturek et al, 1988). Both TGF a and EGF also play central roles in the maintenance of the integrity of the healthy gastric mucosa (Orsini et al, 1993), but EGF production is restricted to mucous neck cells, while extensive local production of TGF a protein and mRNA (Beauchamp et al, 1989) indicate perhaps that TGF a exercises more influence in this organ; Lee et al (1991) found little EGF immunoreactivity in the normal rat oxyntic mucosa, while TGF a immunoreactivity is widespread .…”
Section: Trefoil Peptide Family Of Factorsmentioning
confidence: 99%
“…9) at the plasma membrane, so that in some cases antigenicity at a certain location on the plasma membrane is so intense that individual gold grains can scarcely be perceived; this clustering, optimises the efficiency of the receptor for lateral prox- imation and thus autophosphorylation of the dimer (Van Belzen et al, 1988). Mucous neck cells exhibit the same localization while EGFR immunoreactivity in parietal cells and mucus-secreting pyloric gland cells is even more specifically associated with the basolateral cell membranes (Orsini et al, 1993); thus the activation of the receptor is suggested to have a direct effect on hydrochloric acid production in the stomach (Mori et al, 1987). In normal rat stomach EGFR immunoreactivity is found in proliferative zone cells and some pa-rietal cells (Tarnawski et al, 19921, and in mucous neck cells (Lee et al, 1991).…”
Section: Localisation Of Tgf Cu and Egfrmentioning
confidence: 99%
“…22 The EGF receptor (EGFR) has tyrosine kinase activity and is localized primarily on the basolateral surface of the enterocytes, however, apical EGFR activity has been observed. 23-30 Recent work from our laboratory has shown that the proliferative effects of EGF are preserved despite loss of the enterocyte EGFR, suggesting that EGFR activity in the underlying submucosa and muscularis layers of the bowel may also play a role. 31 The importance of EGF in gut development is highlighted by the fact that global EGFR deletion is associated with embryonic lethality.…”
Section: Introductionmentioning
confidence: 99%